Good Academic Practice During Doctoral Studies - An E-learning Course for Early Career Researchers at the Goethe University, Frankfurt (Germany) - Weigand, Alexander M.; Zimmermann-Timm, Heike (International Journal of Advanced Corporate Learning (iJAC), 2016)
This case study reports on an e-learning course on good academic practice, compulsory for doctoral students of the central graduate academy GRADE at the Goethe University in Frankfurt (Germany). The tool comprises of six closely linked web based trainings. They are designed as a virtual PhD, depicting the different phases of a doctorate and covering the various aspects of good academic practice and potential fields of academic misconduct.